2020
DOI: 10.3390/agriculture10050166
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Soil Enzymes Activity before and after Animal Manure Application

Abstract: Soil enzymes (urease, invertase, acid and alkaline phosphatase) activity in the rhizosphere of field-grown tomato plants were used to monitor the impact of soil amendments (SA) and SA mixed with biochar on soil microbial activity four months after addition of amendments. The soil treatments were sewage sludge (SS); horse manure (HM); chicken manure (CM); vermicompost (worm castings); commercial inorganic fertilizer; commercial organic fertilizer; and no-mulch (NM) native soil used for comparison purposes. Soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 46 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…The amount of P available for plants in the soil is small, constituting only about 1-5% of the total P content [43]. Many authors have suggested that the examination of soil phosphatase activity may indicate the ability of soil to maintain its quality [14,44,[46][47][48][49].…”
Section: Corgmentioning
confidence: 99%
“…The amount of P available for plants in the soil is small, constituting only about 1-5% of the total P content [43]. Many authors have suggested that the examination of soil phosphatase activity may indicate the ability of soil to maintain its quality [14,44,[46][47][48][49].…”
Section: Corgmentioning
confidence: 99%
“…Total metal concentration in soil was extracted using nitric acid (HNO 3 ) as described by Antonious et al [24]. Since total metal concentration in soils is not a useful predictor of bioavailability of soluble metal uptake by plants, a mild solvent (calcium chloride, CaCl 2 ) was also used to extract the readily soluble and extractable metal ions.…”
Section: Metals Extraction and Quantificationmentioning
confidence: 99%
“…Soil quality is significantly dependent on soil biology in which microorganisms play energetic parts in soil fertility and crop production through enzymatic activity, organic matter decomposition, and nutrient cycling. Animal manure is a useful fertilizer for improving soil quality and nutrient status and for reducing dependence on synthetic inorganic fertilizers at low-cost to limited resource farmers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Maerere et al [7] reported that most studies on utilization of animal manure have largely concentrated on crop yield responses with very little attempts to relate such responses with crop varieties and soil enzymes activity following animal manure application. Animal manures applied to soils have a variety of soil microorganisms that release a variety of enzymes responsible for breaking down complex forms of organic materials [1] as well as P, K, Ca, Mg and NO 3 compared to soils to which inorganic fertilizers have been applied [8,9]. Chicken manure (CM) is a cheap natural product that is locally available to organic vegetable growers for use to replace inorganic fertilizers which are relatively expensive and can potentially contaminate natural water resources.…”
Section: Introductionmentioning
confidence: 99%